2020
DOI: 10.3389/fimmu.2020.588245
|View full text |Cite
|
Sign up to set email alerts
|

Extratubular Polymerized Uromodulin Induces Leukocyte Recruitment and Inflammation In Vivo

Abstract: Uromodulin (UMOD) is produced and secreted by tubular epithelial cells. Secreted UMOD polymerizes (pUMOD) in the tubular lumen, where it regulates salt transport and protects the kidney from bacteria and stone formation. Under various pathological conditions, pUMOD accumulates within the tubular lumen and reaches extratubular sites where it may interact with renal interstitial cells. Here, we investigated the potential of extratubular pUMOD to act as a damage associated molecular pattern (DAMP) molecule thereb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 64 publications
0
7
0
1
Order By: Relevance
“…β 2 Integrin activation assay was performed as previously described. 21 Briefly, PAP-1 (10 nM) or vehicle pre-incubated isolated human neutrophils were stimulated with CXCL8 (10 nM) in the presence of either mouse-α-human KIM127 (InVivo, 10 µg µL −1 ) or mouse α-human mAB24 (Hycult Biotech, 10 µg µL −1 ) antibody for 5 min at 37°C in HBSS. Stimulation was stopped by adding ice-cold FACS lysing solution (BD BioScience).…”
Section: Methodsmentioning
confidence: 99%
“…β 2 Integrin activation assay was performed as previously described. 21 Briefly, PAP-1 (10 nM) or vehicle pre-incubated isolated human neutrophils were stimulated with CXCL8 (10 nM) in the presence of either mouse-α-human KIM127 (InVivo, 10 µg µL −1 ) or mouse α-human mAB24 (Hycult Biotech, 10 µg µL −1 ) antibody for 5 min at 37°C in HBSS. Stimulation was stopped by adding ice-cold FACS lysing solution (BD BioScience).…”
Section: Methodsmentioning
confidence: 99%
“…sUmod was reported to interact with myoloid dendritic cells (DCs), monocytes, and neutrophils through toll-like receptor 4 (TLR4), and has an effect on the regulation of inflammation as well as innate immunity [ 30 ], and the immunosuppressive effect of sUmod was achieved by binding to TNF- α and interleukin-1 [ 31 ]. In addition, sUmod stimulated extrarenal tissue, and caused strong inflammatory response, which was characterized by obviously recruiting inflammatory monocytes and neutrophils [ 32 ]. sUmod induced the secretion of TNF- α and the expression of tissue factors in human monocytes, triggered DC maturation through activating NF- κ B and TLR4, and activated protease release, respiratory burst, degranulation, and phagocytosis of neutrophils [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…30 The dysregulation of UMOD expression can result in infiltration of peritubal leukocyte in the kidneys and consequently cause kidney inflammation, which has a strong correlation with the development of frailty. 31 Diabetic kidney disease (DKD) and hypertensive kidney disease (HKD) are prevalent forms of CKD, which are linked to the heredity of the kidneys and the decline in kidney function. Many clinical studies revealed that both DKD and HKD are correlated with an elevated risk of frailty.…”
Section: The Theory Of the Kidney As The Foundation Of Heritability W...mentioning
confidence: 99%
“…reported that UMOD is highly heritable and encodes urinary regulatory protein (Tamm Horsfall protein) in the Henle ring region 30 . The dysregulation of UMOD expression can result in infiltration of peritubal leukocyte in the kidneys and consequently cause kidney inflammation, which has a strong correlation with the development of frailty 31 …”
Section: The Theory Of the Kidney As The Foundation Of Heritability W...mentioning
confidence: 99%